Comparisons of Heat Transfer Enhancement of an Internal Blade Tip with Metal or Insulating Pins (Advances in Applied Mathematics and Mechanics, 2021)
Cooling methods are needed for turbine blade tips to ensure a longdurability and safe operation. A common way to cool a tip is to useserpentine passages with 180-deg turn under the blade tip-cap takingadvantage of the three-dimensional turning effect and impingement likeflow. Improved internal convective cooling is therefore required toincrease the blade tip lifetime. In the present study, augmented heattransfer of an internal blade tip with pin-fin arrays has been investigatednumerically using a conjugate heat transfer method. The computational domainincludes the fluid region and the solid pins as well as the tip regions.Turbulent convective heat transfer between the fluid and pins, and heatconduction within pins and tip are simultaneously computed. The mainobjective of the present study is to observe the effect of the pinmaterial on heat transfer enhancement of the pin-finned tips. It isfound that due to the combination of turning, impingement and pin-fincrossflow, the heat transfer coefficient of a pin-finned tip is a factorof 2.9 higher than that of a smooth tip at the cost of an increased pressuredrop by less than 10%. The usage of metal pins can reduce the tip temperatureeffectively and thereby remove the heat load from the tip. Also, it is foundthat the tip heat transfer is enhanced even by using insulating pins havinglow thermal conductivity at low Reynolds numbers. The comparisons of overallperformances are also included.